The Effect of Prenatal Yoga on Reducing Lower Back Pain in Third-Trimester Pregnancy - Desi Rofita; St Halimatusyaadiah; Ni Nengah Arini Murni (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Pregnancy is a period of significant physiological, social, and emotional transformation, often accompanied by a variety of symptoms, among which back pain is a prevalent complaint. Common intervention for alleviating back pain in pregnant women include light physical activity, such as prenatal yoga or pregnancy specific exercises regiments. This study seeks to elevate the efficacy of prenatal yoga in mitigating back pain during the third trimester of pregnancy.Method: This study utilized a quasi-experimental design employing a non-equivalent control group approach to investigate the impact of prenatal yoga on back pain levels in pregnant women. Participants were 60 women in their third trimester, with 30 assigned to the intervention group (prenatal yoga) and 30 to the control group (pregnancy exercises). Back pain was assessed in both groups using the Numeric Rating Scale (NRS) questionnaire.Result: Both the prenatal yoga and pregnancy exercise groups experienced a reduction in back pain. However, prenatal yoga proved significantly more effective than pregnancy exercises (p < 0.05). Midwives are ideally suited to offer guidance during pregnancy classes to address back pain.